Fast Determination of the Main Reduced Sulfur Species in Aquatic Systems by a Direct and Second-Derivative Spectrophotometric Method - Sébastien Dupraz; Bénédicte Ménez; François Guyot (Journal of Chemistry)
The determination of reduced sulfur species in aquatic systems is not an easy and fast task to accomplish regarding the numerous possible interferences and risks of oxidation that occur with the usual methods of quantification. The method presented here is a direct spectrophotometric method that can be used to quantify sulfides, sulfites, and thiosulfates in a simple and rapid way. The principle is based on the comparison of second-derivative absorbance spectra of the same sample at different pH (9.2, 4.7, and 1.0) and selected absorption wavelengths (250 and 278 nm). This method has been successfully tested and has demonstrated liability to (i) avoid the biases due to absorbance overlaps between the different major chemical species and (ii) keep, as a direct method, the advantages over indirect methods on interferences reduction. The limits of detections (LOD) reached for total sulfide, sulfite, and thiosulfate are 1.37, 7.32, and 1.92 µM, respectively. The method displays low accuracy mean and low relative standard deviation (<4%) as well as a good linearity (R2 > 0.999). Accordingly, this method represents a very robust alternative in terms of cost and rapidity for the quantification of reduced sulfur species in different aquatic environments, from freshwaters to saline and polluted systems.